Handbook on Policing in Central and Eastern Europe
XVI, 316 p.
Keywords: Policing in Central and Eastern Europe has changed greatly since the fall of the Berlin Wall. Some Central and Eastern European countries are constituent members of the European Union, while others have been trying to harmonize with the EU and international requirements for a more democratic policing and developments in accordance with Western European and international policing standards, especially in regard to issues of legality and legitimacy. Changes in the police training system (basic and advanced), internationalization of policing due to transnationalization of crime and deviance, and new police organizational structures and agencies have impacted new cultures of policing (from exclusively state to plural policing). This timely volume examines developments in the last two decades to learn the nature of these changes within Central and Eastern Europe, and their impact on police culture, as well as on society as a whole. The development of police research has varied widely throughout Central and Eastern Europe: in some countries, it has developed significantly, while in others it is still in its infancy. This work allows for a transfer of ideas and models of police organization and policing, with an aim to provide consistent and comparable data across all of the countries discussed. For the twenty countries covered, this systematic work provides: short country-based information on police organization and social control; crime and disorder trends in the last 20 years with an emphasis on policing, police training and police educational systems; changes in policing in the last 20 years; police and the media; present trends in policing (public and private, multilateral, plural policing); policing urban and rural communities; recent research trends in research on policing; and future developments.